Optimization and Scale-up Isolation and Culture of Neonatal Porcine Islets: Potential for Clinical Application. Issue 3 (March 2016) - Ellis, Cara; Lyon, James G.; Korbutt, Gregory S.
One challenge that must be overcome to allow transplantation of neonatal porcine islets (NPIs) to become a clinical reality is defining a reproducible and scalable protocol for the efficient preparation of therapeutic quantities of clinical grade NPIs. In our standard protocol, we routinely isolate NPIs from a maximum of four pancreases, requiring tissue culture in 16 Petri dishes (four per pancreas) in Ham's F10 and bovine serum albumin (BSA). We have now developed a scalable and technically simpler protocol that allows us to isolate NPIs from a minimum of 12 pancreases at a time by employing automated tissue chopping, collagenase digestion in a single vessel, and tissue culture/media changes in 75% fewer Petri dishes. For culture, BSA is replaced with human serum albumin and supplemented with Z-VAD-FMK general caspase inhibitor and a protease inhibitor cocktail. The caspase inhibitor was added to the media for only the first 90 min of culture. NPIs isolated using the scalable protocol had significantly more cellular insulin recovered (56.9 ± 1.4 μg) when compared to the standard protocol (15.0 ± 0.5 μg; p < 0.05). Compared to our standard protocol, recovery of β-cells (6.0 × 10 6 ± 0.2 vs. 10.0 × 10 6 ± 0.4; p < 0.05) and islet equivalents (35, 135 ± 186 vs. 41, 810 ± 226; p < 0.05) was significantly higher using the scalable protocol. During a static glucose stimulation assay, the SI of islets isolated by the standard protocol were significantly lower than the scale-up protocol (4.3 ± 0.2 vs. 5.5 ± 0.1; p < 0.05). Mice transplanted with NPIs using the scalable protocol had significantly lower blood glucose levels than the mice that receiving NPIs from the standard protocol ( p < 0.01) and responded significantly better to a glucose tolerance test. Based on the above findings, this improved simpler scalable protocol is a significantly more efficient means for preparing therapeutic quantities of clinical grade NPIs.